A compact slot antenna with improved bandwidth and gain for wireless applications - Pant, Aadya; ch, Swapna; Bharat, Manish (International Journal of Engineering and Technology, 2018)
A wide-slot antenna is investigated to achieve a bandwidth of about 162%. The ground plane includes a rectangular slot with dual SRR and two semicircular defects in the bottom side of the rectangular slot. A fork like feed-line with two parasitic stubs to increase the bandwidth is used to feed the slot. 37*37*0.8 mm3 is the size of the proposed antenna and the dielectric substrate used is FR4. The measured bandwidth ranges from 1.8-17.5 GHz which is approximately 162%. Significant improvement in gain for the frequency range of 1.8-6.1 GHz is observed. The proposed antenna has radiation patterns that are stable and omnidirectional in both E and H planes in all the six frequency points for entire frequency range. The simulated and measured results are in good agreement.Â Â